De Quervain`s disease: evaluation by high resolution ultrasonography - Das, Abhishek; B. J., Prabhu (International Journal of Research in Medical Sciences, 2017)
Background: De Quervain’s tenosynovitis is a stenosing tenosynovitis of the first extensor compartment of wrist and leads to wrist pain and impaired function of wrist and hand. The aim of this study is to evaluate the role of high resolution ultrasonography in diagnosing suspected cases of de Quervain’s tenosynovitis and also to evaluate the role of high resolution ultrasonography in detecting the anatomical variants of the first extensor compartment which are predisposing conditions for de Quervain’s tenosynovitis. Methods: A prospective study of 15 consecutive cases who were referred with clinical diagnosis of de Quervain`s disease was done with ultrasonography in the department of Radio-diagnosis and findings were carefully analysed. Results: Thickened extensor retinaculum over the first extensor compartment was found in all the cases. Mean thickness of the thickened retinaculum is 1.65 mm. In 60% of cases multiple slips of APL tendon were found. Conclusions: From the study, we conclude that extensor retinaculum thickening is a common finding in de Quervain`s disease.